pH-Induced Transition Between Single-Chain Macrocyclic Amphiphile and [c2]Daisy Chain-Based Bola-Type Amphiphile and the Related Self-Assembly Behavior in Water - Wang, Pi; Wang, Ruihuan; Xia, Danyu (Frontiers in Chemistry, 2020)
Macrocyclic amphiphiles, a type of amphiphiles synthesized based on macrocyclic compounds, have attracted much attention over the past decades due to their unique superiority in the construction of various functional nanomaterials. The regulation of the state of macrocyclic amphiphiles by introducing stimuli-responsive motif to macrocyclic amphiphiles is an efficient way to extend their applications in diverse fields. Herein, pillararene-based macrocyclic amphiphile H1 was prepared. H1 can act as single-chain amphiphile to self-assemble into micelles in water when the pH was ≥5.0. H1 can be protonated to turn into H2 when pH changed to <5.0. Interestingly, H2 formed [c2]daisy chain-based bola-type supramolecular amphiphile. This bola-type supramolecular amphiphile self-assembled into nanosheets in water. Therefore, pH-induced transition between single-chain macrocyclic amphiphile and bola-type amphiphile and the corresponding self-assembly system based on pillararene in water were constructed.